XAV939-mediated ARTD activity inhibition in human MB cell lines. - Cristiano Renna; Roberta Salaroli; Claudia Cocchi; Giovanna Cenacchi (PLoS ONE, 2015)
Diphtheria toxin-like ADP-ribosyltransferases 1 and 5 (ARTD-1, ARTD-5) are poly ADP-ribose enzymes (PARP) involved in non-homologous end-joining (NHEJ), which is the major pathway of double-strand break (DSB) repair. In addition, ARTD-5, or Tankyrase (TNKS), is a positive regulator of the WNT signaling implicated in the development and biological behavior of many neoplasms, such as Medulloblastoma (MB), in which radiotherapy is an essential part of the treatment. The use of radiosensitizing agents may improve the therapeutic index in MB patients by increasing the efficacy of radiotherapy, while reducing toxicity to the neuroaxis. ARTD-5 seems to be a good molecular target for improving the current treatment of MB. In this study, we used the small molecule XAV939, a potent ARTD-5 inhibitor with a slight affinity for ARTD-1, in different human MB cell lines. XAV939 inhibited the WNT pathway and DNA-PKcs in our MB cells, with many biological consequences. The co-administration of XAV939 and ionizing radiations (IR) inhibited MB cells proliferation and clonogenic capacity, decreased their efficacy in repairing DNA damage, and increased IR-induced cell mortality. In conclusion, our in vitro data show that XAV939 could be a very promising small molecule in MB treatment, and these results lay the basis for further in vivo studies with the aim of improving the current therapy available for MB patients.